Educating for Appropriate Design Practice: Insights from Design Innovation. Issue 1 (October 2016) - Dixon, Brian; Murphy, Emma
Abstract : With design disciplines and territories expanding rapidly and design being positioned as a potential means of responding to grand global challenges, graduates of today are increasingly expected to work in dynamic and fluid ways, able to approach any wicked problem creatively. We contend that a design innovation approach is about developing agility and flexibility to be able to respond to any complex scenario where design could be employed or required. Using an action research approach within a single case study, which draws upon a current PGT program in design innovation, we propose that there is value in training students in four key areas: (1) understanding a context before responding, (2) engendering empathy, (3) crafting appropriate research methods, and (4) bringing form to the intangible complex. To illustrate how this is operationalized, we draw on the experiences of a residential student trip, where design innovation master's students worked with cohorts from two international schools. We fully acknowledge that one learning experience, despite being shared by three institutions, does not mean that solid and scalable conclusions can be drawn, but we offer our insights to date for discussion and to inform future learning activities and curriculum designs.